Peningkatan kompetensi guru dalam menyusun RPP daring melalui metode in house training (IHT) - Harnieti Harnieti (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This article aims to analyze the improvement of teacher competence in compiling an Online Learning Implementation Plan (RPP) by applying the In House Training (IHT) method to teachers. The research subjects were teachers who had low competence in compiling online lesson plans with five men and 15 women. This research is a School Action Research which was carried out in two cycles, and each cycle was carried out for two meetings. The data collection technique was carried out by direct observation and accompanied by the vice principal as an observer by using an observation sheet. Then the results of the observations will be analyzed by looking at the increase in each cycle. In the initial conditions, the competence of teachers in preparing online lesson plans was 35.48%. After taking action through In House Training, the competence of teachers in preparing online lesson plans in cycle 1 is 70.42%. An increase in cycle 2 to 87.92% (very good). The results of this study indicate that there is an increase in teacher competence in preparing online lesson plans from cycle 1 to cycle two with an average increase of 17.5%. Based on the results of this study, it can be concluded that the application of the In House Training method can improve the competence of teachers in preparing online lesson plans.